Characterisation of pectins extracted from different parts of Malaysian Durian rinds - Jong, Sze Hui; Abdullah, Norazlin; Muhammad, Norhayati (2021)
Durian rinds are a potential source of pectin. The rinds consist of the outer layer of the fruit which is semiwoody and thorny and the inner layer, which is creamy white. Pectin may be present in varying amounts in different parts of the rind. Previous studies only investigated pectin content from the inner part of the rinds. Therefore, it is essential to provide scientific data on the pectin yield from whole durian rinds (including the thorns). Particularly, this information can be useful when preparing durian rinds for pectin extraction. Hence, this study aims to examine and compare the yield and characteristics of pectin extracted from the inner part (W-I) and whole durian rind (W-H). The results indicate that the pectin yield from W-I was significantly higher (23.97%) than that obtained from W-H. The characterisation results show that both pectins have similar characteristics. The pectins extracted from W-I and W-H were high methoxyl pectin (HMP) with degrees of esterification (DE) at 53.13% and 51.42% respectively. The purity of these pectins was comparable to that of commercial pectins. These findings could pave the way in achieving sustainable pectin production at an industrial scale.